Ultra-stable and tough bioinspired crack-based tactile sensor for small legged robots - Kim, Taewi; Hong, Insic; Kim, Minho; Im, Sunghoon; Roh, Yeonwook; Kim, Chang Hwan; Lim, Jongcheon; Kim, Dongjin; Park, Jieun; Lee, Seunggon; Lim, Daseul; Cho, Junggwang; et al. (npj Flexible Electronics, 2023)
For legged robots, collecting tactile information is essential for stable posture and efficient gait. However, mounting sensors on small robots weighing less than 1 kg remain challenges in terms of the sensor’s durability, flexibility, sensitivity, and size. Crack-based sensors featuring ultra-sensitivity, small-size, and flexibility could be a promising candidate, but performance degradation due to crack growing by repeated use is a stumbling block. This paper presents an ultra-stable and tough bio-inspired crack-based sensor by controlling the crack depth using silver nanowire (Ag NW) mesh as a crack stop layer. The Ag NW mesh inspired by skin collagen structure effectively mitigated crack propagation. The sensor was very thin, lightweight, sensitive, and ultra-durable that maintains its sensitivity during 200,000 cycles of 0.5% strain. We demonstrate sensor’s feasibility by implementing the tactile sensation to bio-inspired robots, and propose statistical and deep learning-based analysis methods which successfully distinguished terrain type.